Muslims in story expanding multicultural understanding through children's and young adult literature - Manglik, Gauri; Siddique, Sadaf (American Library Association, 2018)
Islamophobia is a long standing, deeply entrenched global issue. Targeting the Muslim community was a key part of the Republican agenda in the 2016 U.S. presidential elections and since the Donald Trump's election, this fear of Islam and Muslims is translating into policy as well. Islamophobia disrupts civil society at many levels, from anti Muslim policies such as the travel ban, to heightened tensions and hate crimes across the country, including the increased bullying of Muslim children. One of the key causes of Islamophobia is ignorance, often fueled by negative portrayals of Muslims in media and popular culture. Counter Islamophobia through Stories is a timely and proactive approach to tackling this issue, by engendering friendships and empathy through literature. Our goal is to facilitate a systemic long term change in understanding the diversity of the Muslim experience and to build bridges of understanding and empathy. Exposing children in their formative years to positive stories about Muslims can go a long way to creating a multicultural understanding, and cementing ideas of tolerance, respect and acceptance. Books also help achieve visual diversity by showcasing different foods, dress and traditions. The proposed book will equip librarians to expose all children to Muslim children's books around different themes.